A STUDY OF LINGUISTIC FEACHERES OF PROVERBS IN ENGLISH AND UZBEK LINGUISTICS - Vaisboyeva Barno Vaisboyevna.; F. N. Docent Sobirova. N.K (Western European Studies, 2024)
Folk proverbs, which arose as a unique phenomenon of language, philosophy and artistic creation, are a genre of folklore with a compact form, but deep content. Each one of them shows the beauty of our language, the elegance of our speech, the intelligence and the logic of our thinking with amazing power, and such drops of artistry are a perfect mirror of our people's centuries-old life experiences and everyday life. A study of linguistic features of proverbs in English and Uzbek linguistics was discussed in this article.
Keywords: English; proverb; alliteration; assonance